THE EFFECTIVENESS OF PROJECT BASED LEARNING IN INCREASING STUDENT CREATIVITY IN HIGH SCHOOLS - Rossa Ramadhona; Sidik E. Lahagu (Adisam Publisher, 2025)
This research aims to examine the effectiveness of project-based learning (PBL) in increasing student creativity in senior high schools. The method used is a literature review, where data is obtained through reviewing scientific articles, textbooks and other reliable sources relevant to the topic. In this research, the concept of student creativity is discussed as the ability to produce original and valuable ideas, which is an important indicator in assessing creativity in a learning context. Project-based learning is analyzed as a learning approach that puts students at the center of learning, allowing them to explore, collaborate, and implement ideas in real projects to solve complex problems. The effectiveness of PBL in increasing student creativity is measured through achievements in problem solving, collaborative abilities, and the development of critical and creative thinking abilities. The results of the literature review show that PBL plays a significant role in increasing students' creativity, as a result of their exposure to learning situations that require the application of knowledge in real contexts and active collaboration between students. The conclusions of this study emphasize the importance of integrating project-based learning in school curricula to support the development of students' creativity and problem-solving abilities, which can better prepare them for real-world challenges.